Design and testing for shape control of piezoelectric structures using topology optimization. (15th August 2015) - Luo, Quantian; Tong, Liyong
Highlights: Novel forms of response function for shape control of PZT structures using MIST. An efficient design update algorithm via searching for iso-surface threshold level. Experimental validation on optimum topological designs for shape control PZT plates. Abstract: This paper presents a numerical and experimental investigation into optimum topological design of morphing piezoelectric structures using a moving iso-surface threshold method. Proposed first is a novel formulation of the response function suitable for minimizing the error norm between desired and achieved shapes in the form of combined mutual strain energy densities. A design updating algorithm with an enhanced efficiency is then developed in searching for the optimum iso-surface threshold during iterations. Numerical results are presented for optimum topological material distribution for shape morphing of piezoelectric plates subjected to mechanical loading, one channel electrical voltage and a combination of both mechanical and electrical loadings. Experiments for selected optimal topological designs are conducted to validate the present response function and updating algorithm as well as the numerical results.